The impact of preoperative education in satisfaction and postoperative outcomes of patients undergoing cardiac surgery - Kalogianni, Antonia; Georgiadis, Georgios; Katselou, Olga; Kadda, Olga; Sotiropoulou, Aikaterini; Argiriou, Mihalis (Health & Research Journal, 2019)
Introduction: The effectiveness of preoperative education in postoperative course of cardiac surgery patients has been questioned. Aim: To estimate the impact of preoperative education in satisfaction and postoperative outcomes of patients undergoing cardiac surgery. Material and Method: A quasi-experimental trial was conducted. Sixty nine patients who admitted for elective cardiac surgery were divided randomly in intervention (34) and control group (35). Intervention group received written and verbal education based on patient centered communication by specially trained nurses. Patients’ satisfaction, postoperative complications and hospital length of stay (LOS) was measured. Results: Scores on all dimensions of satisfaction were greater for intervention group (p<0,001).No difference found for complications in intensive care unit (ICU) (p=0,150) in both groups. The total complications was lower (p=0,028) in intervention group with a lower proportion of arrhythmia (p=0,011). The median LOS in ICU was shorter for intervention group (p=0,035). No difference found in median hospital LOS in either group. Conclusions: Nurse-led preoperative education increases satisfaction of patients undergoing cardiac surgery and may have an effect on LOS shortening and complications control.